2022
DOI: 10.3389/fmed.2022.844728
|View full text |Cite
|
Sign up to set email alerts
|

Nitazoxanide in Patients Hospitalized With COVID-19 Pneumonia: A Multicentre, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: BackgroundNitazoxanide exerts antiviral activity in vitro and in vivo and anti-inflammatory effects, but its impact on patients hospitalized with COVID-19 pneumonia is uncertain.MethodsA multicentre, randomized, double-blind, placebo-controlled trial was conducted in 19 hospitals in Brazil. Hospitalized adult patients requiring supplemental oxygen, with COVID-19 symptoms and a chest computed tomography scan suggestive of viral pneumonia or positive RT-PCR test for COVID-19 were enrolled. Patients were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 21 publications
2
45
0
Order By: Relevance
“…The search strategy yielded 1031 potentially relevant records. After screening of titles and abstracts and evaluation of completed trials retrieved from ClinicalTrials.gov, eight full-text articles were assessed for eligibility, and five [ 23 27 ] blinded, placebo-controlled RCTs were included in the meta-analysis. A flow diagram of the study selection process and specific reasons for exclusion are detailed in the supplement (eFig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy yielded 1031 potentially relevant records. After screening of titles and abstracts and evaluation of completed trials retrieved from ClinicalTrials.gov, eight full-text articles were assessed for eligibility, and five [ 23 27 ] blinded, placebo-controlled RCTs were included in the meta-analysis. A flow diagram of the study selection process and specific reasons for exclusion are detailed in the supplement (eFig.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in the USA, Puerto Rico, Brazil, and Argentina and included individuals with mild to moderate COVID-19 [ 24 27 ] or requiring supplemental oxygen therapy [ 23 ]. All trial protocols were registered on ClinicalTrials.gov, had a parallel design, and were classified as Phase 2 or Phase 3.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have recommended the use of nitazoxanide for patients with COVID-19 in low-and middle-income countries due to its low cost, large availability, and safety. Individual results have shown that nitazoxanide can reduce the viral load during the rst week of treatment [19,20], the levels of some in ammatory mediators including CRP and D-dimer [17,21], the time for hospital discharge [17,21], and the time to sustained clinical response [18] in patients with mild to moderate COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Search strategy yielded 1,031 potentially relevant records. After screening of titles and abstracts and evaluation of completed trials retrieved from ClinicalTrials.gov, eight full-text articles were assessed for eligibility and ve [17][18][19][20][21] blinded, placebo-controlled RCTs were included in the meta-analysis. A ow diagram of the study selection process and speci c reasons for exclusion are detailed in the Supplement (eFig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation